The influence of various factors on the photodegradation of methyl orange in the presence of titanium dioxide and β-cyclodextrin derivatives - Opanasenko, O.A.; Riabov, S.V.; Sinelnikov, S.I.; Kercha, Yu.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
The photodegradation process of methyl orange is studied in the presence of TiO2 and β-cyclodextrin, and its derivatives. It is found that β-CD's maleates and acrylates significantly increase the intensity of this process (about 1.5–2 times). The factors such as pH of the medium, the concentration and surface-active properties of β-CD derivatives, which influence the process of passing dye photodegradation were investigated. The results obtained indicate that the optimum pH of the medium for effective methyl orange destruction ranges from 3 to 5. A direct relationship between the individual parameters of surface-active characteristics of β-CD derivatives is established.